Column Mode Study to Evaluate The Behavior of Metal Adsorption of Phosphoric Adsorbent Synthesized by Radiation Induced Graft Polymerization - Fatmuanis Basuki; Noriaki Seko; Masao Tamada (BATAN, 2004)
ABSTRACT Column mode study were performed to evaluate the behavior of fibrous adsorbent having phosphoric function prepared by directly synthesis of 2-hydroxyethyl methacrylate phosphoric acid onto polypropylene coated polyethylene by radiation induced graft polymerization. The parameter observed was effect of pH, adsorbent form, metal concentration, flow rate and degree of grafting. The higher degree of grafting obtained was 427% which correspond to 5.2 mmol phosphoric content. In the column mode adsorption of Pb by using column packed with phosphoric adsorbent, the optimum pH found was 6 and the breakthrough curve Na and H form of adsorbent was similar, meaning the same behavior of adsorbent kinetics. The breakthrough point and curve do not strongly depend on flow rates which indicate that the adsorbent has a high adsorption rate. The adsorbent also has good ability to adsorb Pb, Cd, Co and Zr. The highest adsorption capacity obtained was 4.2 mmol/g adsorbent for Pb and Zr. ABSTRAK Studi mode column dilakukan untuk mengevaluasi sifat-sifat dari adsorbent serat yang memiliki gugus fungsi phosphor. Serat adsorbent disintesis langsung dengan cara polimerisasi cangkok monomer 2-hydroxyethyl methacrilate phosphoric acid pada serat polipropilene yang di coating poliethylene dengan menggunakan radiasi. Parameter yang diteliti adalah pengaruh dari pH, tipe adsorbent, konsentrasi logam, kecepatan alir dan persen grafting. Persen grafting tertinggi yang diperoleh adalah 427% setara kandungan phosphor sebanyak 5.2 mmol. Adsorpsi metoda column dengan menggunakan column packing yang mengandung adsorbent bergugus fungi phosphor untuk logam Pb diperoleh pH optimum adalah 6 dan breakthrough dari adsorbent tipe Na dan H adalah sama atau keduanya memiliki kesamaan kinetika penyerapan. Kurva dan titik breakthrough tidak secara kuat dipengaruhi oleh kecepatan alir, hal ini menandakan adsorbent memiliki kecepatan penyerapan yang tinggi. Adsorben memiliki kemampuan penyerapan yang baik terhadap Pb, Cd, Co dan Zr. Kapasitas penyerapan tertinggi adalah 4.2 mmol/gram penyerap untuk Pb dan Zr.